Banganga tank on Malabar Hill in Mumbai - Banganga by Ghosh, Ayan (2023)
Located on Malabar Hill, Banganga Tank is the oldest and largest surving Hindu place of pilgrimage in Mumbai, still in its historical location. The tank has been a tirthasthan (place of pilgrimage) at least since the 12th century and stories of its origin even earlier, mentioned in the Skanda Purana. It is believed Lord Rama visited the site during his search for Sita.